On the relation between polarimetric synthetic aperture radar (SAR) features and sea ice melt pond fraction - Fors, Ane Schwenke; Doulgeris, Anthony Paul; Renner, Angelika; Brekke, Camilla; Gerland, Sebastian (2015 IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2015)
In this study we examine the relationship between sea ice melt pond fraction and two polarimetric C-band synthetic aperture radar (SAR) features. Three high-resolution SAR scenes were recorded in the Fram Strait in late summer 2011, covering iceberg-fast first-year and old sea ice. In addition, melt pond fraction was retrieved from photographs recorded during a helicopter flight at the study area. Co-polarisation ratio and relative kurtosis were extracted from the SAR scenes and compared to the retrieved melt pond fraction. A correlation between relative kurtosis and melt pond fraction was found in all scenes. Co-polarisation ratio was correlated to melt pond fraction in one of the scenes. Refreezing of the melt ponds could explain the lack of correlation in the two other scenes. Our results demonstrate a potential of high resolution C-band SAR for retrieval of melt pond fraction, a valuable parameter in climate model parametrization and climate studies.